(3efXheI aj Gdabg GdTGaYis - (3EHQGgje GdYGQjs
(3ChdgG (B:s
(3cJGH GdWgGQI ejGggG ZOJ dgG CbSGe WghQ Ch WGgQ jG EeGe Ch fLS hGdQGHY GdecQhg aNP HjGf Gdcd HGabjg s
(3BNQgG (B:s
(3eMeO Pi GdeYLRGJ GdHGgQI efbPfG ef ghd jhe GdBNQI hGdBd hGdUMH HgPG CNJe fXei hGddg JYGdi CYde s
(3HChdgG hbajI HGSe YdGeI HjQhJ eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQNI SfI (B1373 (3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJ CSeGA GdCHhGH HGdMeQIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdTGaYjs